Green Islamic Finance: Sustainable Financing Strategies from the Perspective of Maqasid al-Shariah - Ita Marianingsih (PAPUA: International Journal of Sharia Business Management, 2025)
This study explores the integration of maqāṣid al-sharīʿah (the higher objectives of Islamic law) into green Islamic finance as a response to the growing global call for sustainable economic models. Despite increasing discourse on sustainable finance, the operationalization of environmental ethics within the Islamic financial system remains underdeveloped. The research addresses this gap by examining how key maqāṣid principles such as the preservation of life (ḥifẓ al-nafs), wealth (ḥifẓ al-māl), and the environment (ḥifẓ al-bi’ah) can guide the development of Shariah-compliant green financial instruments. Using a qualitative, exploratory research design, data were collected through in-depth interviews with Islamic finance scholars and practitioners, along with document analysis of regulatory fatwas and sustainability reports. Thematic analysis revealed four key findings: strategic alignment between Shariah and environmental goals; institutional innovation and readiness; persistent barriers in regulation, culture, and knowledge; and the potential of a maqasid-based model to lead sustainable financial reform. The study concludes that while the foundations of green Islamic finance are normatively strong, actual implementation requires regulatory clarity, capacity development, and inter-disciplinary collaboration. This research contributes to both theory and practice by offering a conceptual framework for embedding Islamic ethical values into modern financial systems, demonstrating that Islamic finance can serve not only as an ethical alternative but as a transformative model in achieving the Sustainable Development Goals (SDGs).